The Influence of Quizizz Game Media on Interest in Learning Arabic in Class 10 Students of SMA Muhammadiyah 3 Reinforcement: Pengaruh Media Permainan Quizizz Terhadap Minat Belajar Bahasa Arab Siswa Kelas 10 Bahasa SMA Muhammadiyah 3 Tulangan - Mumtaz, Shafira; Ammar, Farikh Marzuki (Universitas Muhammadiyah Sidoarjo, 2022)
This research was motivated by the existence of a pandemic in Indonesia, so that the learning process was disrupted. As a result, many students lose interest in learning because distance learning and learning methods and media are still simple. The purpose of this study was to determine whether there was an influence on the interest in learning Arabic for class X Language of SMA Muhammadiyah 3 Tulangan and how big the effect was. The research method used is quantitative with a correlational approach. Methods of data analysis using hypothesis testing and correlation coefficient test. The results showed that the significant value of the hypothesis test results was 0.040 < 0.05, so Ho was rejected. So, variable X (Quizizz) has an effect on variable Y (Interest in learning Arabic). The effect of variable X on variable Y is positive with a correlation level of 0, 214 or 21.4%. This concludes that there is a significant effect of the Quizizz variable on the variable of interest in learning Arabic for class X Language at SMA Muhammadiyah 3 Tulangan.